The Antioxidant, Antimicrobial, and Cytotoxic Properties of Garcinia mangostana L. Peel Extracts and Their Alpha-Mangostin Content - John, Oliver Dean; Mojulat, Monjia Belleza Cosmas; Henry, Eunice Lua; Ng, Kai Song; Tan, Sheri-Ann; Surugau, Noumie (Jordan Journal of Pharmaceutical Sciences, 2025)
Garcinia mangostana L. (mangosteen) peel is widely used as a traditional medicine in Southeast Asia, known for its beneficial biological properties. This study assessed the optimal extraction solvent for a-mangostin from the peel of G. mangostana using 70 % ethanol, 70 % acetone, 80 % methanol, and water at room and boiling temperatures. Furthermore, the most optimal extract’s antioxidant and antimicrobial properties were studied. The 70% ethanol and 70% acetone solvents produced the highest a-mangostin recovery, but the 70% ethanol showed higher flavonoid and anthocyanin contents than 70% acetone. The ethanolic extract showed moderate antimicrobial activity against Escherichia coli and Staphylococcus aureus. The brine shrimp larvae toxicity assay showed that the organic solvents were toxic at 100 µg/mL. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that 400 μg/ml of 70 % ethanolic extract was toxic to the HepG2 cells. When challenged with tert-butyl hydroperoxide (t-BOOH)-induced oxidative stress, the ethanolic G. mangostana extract from concentrations 12.5 to 50 µg/mL showed protective effects against this oxidative stimulation. This study showed that the 70% ethanolic extract of G. mangostana peel showed optimal recovery of a-mangostin and other phytochemicals while showing protective effects against oxidative stimulations in HepG2 cells.